Presentation - Rodríguez Chávez, Iván (2021)
The present issue of Archivo Vallejo gathers the first part of a group of articles that were exhibited at the IV International Congress "Vallejo Siempre", in New York, from September 30 to October 2, 2021. This event was also a heartfelt tribute to the American poet Clayton Eshleman (1935-2021), notable translator of our beloved poet César Vallejo.